(untitled) (Canadian Medical Education Journal, 2022)
Implication Statement Reflective practice is important for learning, accurate self-assessment, and fostering a growth mindset as a resident physician. To help identify candidates with these traits, we designed a multiple mini interview (MMI) station to prompt applicants to demonstrate critical reflection of their performance on an unfamiliar task and provide a self-assessment. The results show us that this station had clear consequences in the eventual rank list of candidates suggesting that it might provide valuable insight for selection committees to identify applicants who lack skills in self-reflection.